The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/trf.16354
|View full text |Cite
|
Sign up to set email alerts
|

The role of early natural killer cell adoptive infusion before engraftment in protecting against human herpesvirus‐6B encephalitis after naïve T‐cell‐depleted allogeneic stem cell transplantation

Abstract: Background Naïve T‐cell‐depleted grafts have been employed as an ex vivo T‐cell depletion (TCD) platform to prevent graft‐versus‐host disease (GvHD) and improve immune reconstitution by providing rapid donor memory T‐cell reconstitution after allogenic hematopoietic stem cell transplantation (allo‐HSCT). CD45RA− memory T cells confer protection against viruses such as cytomegalovirus, Epstein–Barr virus, and adenovirus; however, reports have shown an unexpectedly high incidence of human herpesvirus (HHV)‐6B en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…NK cells and ILC1 differ mainly in their function; while ILC1 is weakly cytotoxic, NK cells are dedicated cytotoxic cells [ 10 ]. Their function is to defend the organism from viral infections [ 11 ], such as Epstein–Barr virus [ 12 ], varicellA−zoster virus [ 13 ], cytomegalovirus (CMV) [ 14 ] or herpesvirus‐6B [ 15 ] as well as fighting against malignant cells [ 16 ]; they have been reported to get to a functional exhaustion level along with disease progression, characterized by elevated expression of regulatory receptors such as PD1 and CD244 [ 17 ], lower levels of CD16 marker [ 18 ] and/or higher levels of NKG2A marker [ 19 ]. Peripheral blood NK cells can be divided in two different subsets regarding the expression of CD56: CD56bright and CD56dim cells [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…NK cells and ILC1 differ mainly in their function; while ILC1 is weakly cytotoxic, NK cells are dedicated cytotoxic cells [ 10 ]. Their function is to defend the organism from viral infections [ 11 ], such as Epstein–Barr virus [ 12 ], varicellA−zoster virus [ 13 ], cytomegalovirus (CMV) [ 14 ] or herpesvirus‐6B [ 15 ] as well as fighting against malignant cells [ 16 ]; they have been reported to get to a functional exhaustion level along with disease progression, characterized by elevated expression of regulatory receptors such as PD1 and CD244 [ 17 ], lower levels of CD16 marker [ 18 ] and/or higher levels of NKG2A marker [ 19 ]. Peripheral blood NK cells can be divided in two different subsets regarding the expression of CD56: CD56bright and CD56dim cells [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in our institutional cohort of pediatric patients who underwent haplo transplants using CD45RA + depletion followed by NK cell addback, we did not observe a high incidence of HHV-6 encephalitis. In keeping with the in vitro findings and encouraged by the results of our study, the same group of investigators in Spain performed a follow-up study wherein they incorporated a NK-cell infusion within 10 days after a CD45RA +depleted transplant (48). The goal was to infuse a number of NK cells equivalent to at least twice the number of CD4 + T cells infused with the CD45RA + -depleted fraction, as in vitro work showed that NK cells could eliminate HHV-6B CD4 + T cells when present at a ratio of 2:1 (53).…”
Section: Haploidentical Donorsmentioning
confidence: 66%
“…4 , 15 We and other authors have shown the antiviral properties of CD45RA − memory T cells in hematopoietic stem cell transplantation and COVID-19 settings. 25 , [38] , [39] , [40] , [41] We have demonstrated the safety and feasibility of adoptive cell therapy using CD45RA − memory T cells containing SARS-CoV-2 specific T cells in hospitalized COVID-19 patients. In this approach, we pursued to increase the pool of lymphocytes in patients with lymphopenia, exerting an antiviral effect on the coronavirus and protecting the patient from other viruses that the donor encountered.…”
Section: Discussionmentioning
confidence: 91%